How can we know what we don't know? An exploration of professionals' engagement with complicated grief. Issue 5 (May 2022) - Dodd, Anne; Guerin, Suzanne; Delaney, Susan; Dodd, Philip
Highlights: Integrated findings from mixed methods study on complicated grief. Complicated grief research and professional practice are not aligned. Professionals' confidence in their ability to work in this area is overstated. Knowledge exchange between grief researchers and practitioners needs development. Abstract: Objective: Research has shown that complicated grief has the potential to adversely affect bereaved individuals, and in this context, understanding how mental health professionals engage with it in practice is of relevance. Gaining an understanding of professionals' knowledge, attitudes, skills and training in relation to complicated grief could provide insights that will inform their training and professional development. The aim of this study was to consider professionals' engagement with complicated grief, as represented by self-reported knowledge, attitudes, skills and training. Methods: The study used a three-phase mixed methods design (systematic review, qualitative interviews, and a quantitative survey) with empirical data being collected from psychologists, psychiatrists and counselor/psychotherapists. Results: Analysis yielded 15 integrated findings across the three phases, which were grouped into two clusters: the first highlighted tension between professionals' reported confidence and competence and the second explored the parameters and contribution of research and training in this area. Conclusion: Professionals' perception of their competence to work with complicated grief seems overstated and research and professional practice are not aligned. Practice implications: These findings are positioned to inform empirically supported training that addresses identified deficits in professionals' knowledge, attitudes and skills. It is important therefore that training is reflective of the needs of different professional groups.